2009
DOI: 10.1002/pca.1157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metabolic variation and galanthamine content in Narcissus bulbs by 1H NMR

Abstract: Since useful qualitative and quantitative information about the metabolic state of Narcissus bulbs can be obtained by (1)H NMR, this method is useful for agricultural applications, and for quality control of raw material used in the pharmaceutical industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…This was especially true for the series of isomeric substances formed under photolytic conditions. However, most of the fragments found were in good agreement with previously published data [13][14][15]. Due to this, NMR spectroscopy was additionally employed wherever possible to elucidate the structures of the formed degradation products.…”
Section: Structural Elucidation Of Degradation Productssupporting
confidence: 75%
“…This was especially true for the series of isomeric substances formed under photolytic conditions. However, most of the fragments found were in good agreement with previously published data [13][14][15]. Due to this, NMR spectroscopy was additionally employed wherever possible to elucidate the structures of the formed degradation products.…”
Section: Structural Elucidation Of Degradation Productssupporting
confidence: 75%
“…11 The amount of galantamine also varied from 2.36 mg/g dw to 3.32 mg/g dw in N. pseudonarcissus bulbs collected from the Netherlands. 10 According to our results, galantamine content of the Sternbergia species was lower than that of L. aestivum when they were compared. The current study's results revealed that Sternbergia species are not valuable sources for galantamine extraction.…”
Section: 26mentioning
confidence: 92%
“…8 In another study conducted on L. aestivum, an acetonitrile:methanol:buffer pH 4.5 (10:10:80) mixture was used for elution on an RP-C18 column to determine galantamine amount. 9 Lubbe et al 10 also reported HPLC analysis of galantamine in Narcissus pseudonarcissus on a C18 column using 10% (v/v) acetonitrile in water containing 0.1% trifluoroacetic acid (TFA) as mobile phase. Galanthus elwesii was also analyzed for its galantamine content by using a mobile phase comprising a TFA:water:ACN (0.01:90:10) mixture on an RP-C18 column.…”
Section: Introductionmentioning
confidence: 99%
“…Galanthamine (GAL) in BLR is a major biologically active ingredient (Fig. 1), and is used as a cholinergic drug for the treatment of Alzheimer's disease by inhibiting acetylcholinesterase and positively modulating nicotinic acetylcholine receptors [1,2]. Determinations of GAL in pharmaceutical products, biological fluids and tissue samples have been reported with the aid of various techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Determinations of GAL in pharmaceutical products, biological fluids and tissue samples have been reported with the aid of various techniques (e.g. nuclear magnetic resonance [1], HPLC [3,4] and LC [2,5,6], gas chromatography and CE [7,8], capillary gas chromatography-mass spectrometry [9], CE-mass spectrometry [10], MEKC-UV [11], flow injection [12], and radioimmunoassay [13]). The combination of electrochemiluminescence (ECL) and CE offers many advantages such as high selectivity, good efficiency, fast analysis speed, and easy operation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%